Comparison of two quantitative fit-test methods using N95 filtering facepiece respirators. Issue 8 (2nd August 2016) - Sietsema, Margaret; Brosseau, Lisa M.
ABSTRACT: Current regulations require annual fit testing before an employee can wear a respirator during work activities. The goal of this research is to determine whether respirator fit measured with two TSI Portacount instruments simultaneously sampling ambient particle concentrations inside and outside of the respirator facepiece is similar to fit measured during an ambient aerosol condensation nuclei counter quantitative fit test. Sixteen subjects (ten female; six male) were recruited for a range of facial sizes. Each subject donned an N95 filtering facepiece respirator, completed two fit tests in random order (ambient aerosol condensation nuclei counter quantitative fit test and two-instrument real-time fit test) without removing or adjusting the respirator between tests. Fit tests were compared using Spearman's rank correlation coefficients. The real-time two-instrument method fit factors were similar to those measured with the single-instrument quantitative fit test. The first four exercises were highly correlated (r > 0.7) between the two protocols. Respirator fit was altered during the talking or grimace exercise, both of which involve facial movements that could dislodge the facepiece. Our analyses suggest that the new real-time two-instrument methodology can be used in future studies to evaluate fit before and during work activities.